INTERNET-BASED ACTIVITIES IN DEVELOPING STUDENTS’ ENGLISH SKILLS - Ardi, Havid (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2012)
The development of Information Technology (IT) challenges the teacher to use the facility to create interesting and motivating activities in learning English. This article explores how the teachers can use various materials and facilities supported by the new IT to support their students in learning English and to practice their English in authentic environment. The activities incorporate internet-based activities as media to practice integrated-skills in the foreign language. The study seeks to determine the usefulness of using email, blogs, and facebook as current communication media that are available in the internet to facilitate students in learning English both inside and outside the classroom.Â